2017
DOI: 10.1016/j.jfda.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus pentosus GMNL-77 inhibits skin lesions in imiquimod-induced psoriasis-like mice

Abstract: Psoriasis, which is regarded as a T-cell-mediated chronic inflammatory skin disease, is characterized by hyperproliferation and poor differentiation of epidermal keratinocytes. In this study, we aimed to determine the in vivo effect of a potentially probiotic strain, Lactobacillus pentosus GMNL-77, in imiquimod-induced epidermal hyperplasia and psoriasis-like skin inflammation in BALB/c mice. Oral administration of L. pentosus GMNL-77 significantly decreased erythematous scaling lesions. Real-time polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 36 publications
1
77
1
6
Order By: Relevance
“…Other studies conducted in humans confirmed this hypothesis [76-78]. Thus, probiotics may be efficient in acne and other inflammatory skin diseases such as atopic dermatitis and potentially psoriasis [79-83]. …”
Section: Resultsmentioning
confidence: 79%
“…Other studies conducted in humans confirmed this hypothesis [76-78]. Thus, probiotics may be efficient in acne and other inflammatory skin diseases such as atopic dermatitis and potentially psoriasis [79-83]. …”
Section: Resultsmentioning
confidence: 79%
“…Total RNA was isolated using TRIzol (Invitrogen, Shanghai, China) and applied to synthesize first‐strand complementary DNA at 25 °C for 60 min and 70 °C for 15 min with random hexamers and Moloney murine leukemia virus reverse transcriptase (Promega, Corporation, Madison, USA). The quantitative polymerase chain reaction (PCR) was performed using the EzOmice SYBR Qpcr kit (Vazyme Biotech Co. Ltd, Nanjing, China), using an ABI StepOnePlus Real‐time PCR System (Applied Biosystems, Carlsbad, CA, USA) . The primer sequences of glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), IL‐6, IL‐12 p40, IL‐1 α , IL‐1 β , chemokine (C‐X‐C motif) ligand 1 (CXCL1) and chemokine (C‐C motif) ligand 3 (CCL3) for coding sequence are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative polymerase chain reaction (PCR) was performed using the EzOmice SYBR Qpcr kit (Vazyme Biotech Co. Ltd, Nanjing, China), using an ABI StepOne-Plus Real-time PCR System (Applied Biosystems, Carlsbad, CA, USA). 22 The primer sequences of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), IL-6, IL-12 p40, IL-1 , IL-1 , chemokine (C-X-C motif ) ligand 1 (CXCL1) and chemokine (C-C motif ) ligand 3 (CCL3) for coding sequence are summarized in Table 1.…”
Section: Expression Of Inflammatory Cytokines and Chemokines Of Murinmentioning
confidence: 99%
“…To date, studies investigating the role of probiotics in psoriasis are lacking, although there is some evidence that probiotics may exert beneficial immunoregulatory effects by reducing inflammation. 66,67 In patients with psoriasis, oral administration of Bifidobacterium infantis for 8 weeks led to significantly decreased levels of inflammatory C-reactive protein and tumour necrosis factor-a, although it is unclear whether this was accompanied by clinical improvements. 67 However, in a mouse model of psoriasis, oral administration of Lactobacillus pentosus GMNL-77 reduced tumour necrosis factor-a and IL-23-IL-17 axis cytokines, which was associated with decreased erythematous scaling lesions.…”
Section: Psoriasismentioning
confidence: 99%
“…67 However, in a mouse model of psoriasis, oral administration of Lactobacillus pentosus GMNL-77 reduced tumour necrosis factor-a and IL-23-IL-17 axis cytokines, which was associated with decreased erythematous scaling lesions. 66 More research exploring the role of the microbiome and its modulation as a therapy in psoriasis would be complementary to the many ongoing immunological treatment studies.…”
Section: Psoriasismentioning
confidence: 99%